DDR2–CYR61–MMP1 Signaling Pathway Promotes Bone Erosion in Rheumatoid Arthritis Through Regulating Migration and Invasion of Fibroblast‐Like Synoviocytes. (3rd November 2016) - Huang, Tong‐Lie; Mu, Nan; Gu, Jin‐Tao; Shu, Zhen; Zhang, Kuo; Zhao, Jin‐Kang; Zhang, Cun; Hao, Qiang; Li, Wei‐Na; Zhang, Wang‐Qian; Liu, Nan‐Nan; Zhang, Yong; et al.
ABSTRACT: Regulation of matrix metalloproteinases (MMPs) by collagen in the fibroblast‐like synoviocytes (FLSs) plays a critical role in joint destruction in rheumatoid arthritis (RA). Our previous study indicated that discoidin receptor 2 (DDR2) mediated collagen upregulation of MMPs. However, the precise underlying mechanism remains unclear. We report here that CYR61, a secreted, extracellular matrix–associated signaling protein which is capable of regulating a broad range of cellular activities, including cell adhesion, migration, proliferation, and apoptosis, is significantly upregulated in collagen II–stimulated RA FLS. Further studies found that collagen II–activated phosphorylated‐DDR2 induces CYR61 through activation of transcription factor activator protein 1 (AP‐1). The elevated CYR61, in turn, accelerates MMP1 production via ETS1 (ETS proto‐oncogene 1). In addition, CYR61 significantly promotes FLS invasion and migration. Blockade of CYR61 by an adenovirus expressing CYR61 shRNA (Ad‐shCYR61) in vivo remarkably ameliorated the severity of arthritis, reduced inflammatory cytokine secretion, and attenuated bone erosion as detected by micro–computed tomography (μCT), in collagen‐induced arthritis (CIA) rats. Taken together, we uncovered the Collagen II–DDR2–AP‐1–CYR61–ETS1–MMP1 loop in RA FLS. In which, CYR61 acts as a hinge to promote cartilage damage through regulating FLS invasion, migration, and MMP1 production and the inflammatory cascade in RA. Thus, CYR61 may be a promising diagnostic and therapeutic target for RA treatment. © 2016 American Society for Bone and Mineral Research.